2016
DOI: 10.1128/jvi.00674-16
|View full text |Cite
|
Sign up to set email alerts
|

HIV DNA Is Frequently Present within Pathologic Tissues Evaluated at Autopsy from Combined Antiretroviral Therapy-Treated Patients with Undetectable Viral Loads

Abstract: HIV infection treatment strategies have historically defined effectiveness through measuring patient plasma HIV RNA. While combined antiretroviral therapy (cART) can reduce plasma viral load (pVL) to undetectable levels, the degree that HIV is eliminated from other anatomical sites remains unclear. We investigated the HIV DNA levels in 229 varied autopsy tissues from 20 HIV-positive (HIV ؉ ) cART-treated study participants with low or undetectable plasma VL and cerebrospinal fluid (CSF) VL prior to death who w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
128
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 138 publications
(140 citation statements)
references
References 97 publications
9
128
1
2
Order By: Relevance
“…Although the medical information reported here is complete to the best of our ability, some clinical variables are unknown. The precise location of tissue sampling could clearly impact HIV recovery; for example, Lamers et al (16) found high variability in the amount and detection of HIV in tissues could within an individual. We used a sequencing technique (singlegenome sequencing) and multiple extractions and amplifications in order to ensure that we sampled the broadest variability possible, but deep-sequencing studies could provide even more resolution.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although the medical information reported here is complete to the best of our ability, some clinical variables are unknown. The precise location of tissue sampling could clearly impact HIV recovery; for example, Lamers et al (16) found high variability in the amount and detection of HIV in tissues could within an individual. We used a sequencing technique (singlegenome sequencing) and multiple extractions and amplifications in order to ensure that we sampled the broadest variability possible, but deep-sequencing studies could provide even more resolution.…”
Section: Discussionmentioning
confidence: 99%
“…Most participants are recruited premortem; however, the remains of very recently deceased individuals may be donated by legal heirs, in which case information is obtained from guardians and/or by authorized release of medical records. Extensive details concerning NNAB guidelines, questionnaires and medical assessments are available in reference 16.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations